PENGARUH KUALITAS PRODUK DAN RESIKO TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN JAMU MADURA ( STUDI KAT DI UD JAMU UMMI KULSUM SUMENEP) - Wahyuni, Purwati Ratna; Rahman, Sindi Arista; Hopid, Hopid (Universitas Islam Madura, 2025)
This study aims to observe and analyze the relationship between product quality variables and risks on the decision making of Madura herbal medicine at UD Jamu Ummi Kulsum Sumenep. This study uses a quantitative descriptive method. Data collection was carried out by distributing questionnaires to a number of consumers of UD Jamu Ummi Kulsum Sumenep. Using the SPSS tool version 26. Random sampling technique. Through statistical tests, it is observed whether the variables of product quality and risk are normally distributed. Through the acquisition of the t-test, it shows that the product quality variable has a significant influence on the purchase decision and the risk variable has a significant influence on the purchase decision. However, the results of the f test with others said that the variables of product quality and risk had a strong relationship with positive and significant impact on the purchase decision of Jamu Madura at UD Jamu Ummi Kulsum Sumenep.